A Reputational Model of Authority - Nabil I. Al-Najjar (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1998)
: The paper provides a model where authority relationships are founded on reputation. The viability of authority is the result of subordinates' free-riding on each other challenges, reducing the frequency of challenges, and making reputations worth defending. The party with authority secures subordinates' compliance through the payment of rents to influence the extent of their failure to act collectively and exacerbate the free-rider problem they face. The model provides a framework to explain how the magnitude and form of these rents depend on the primitives of the environment and on the authority's design of its reputation. Applications to efficiency wages, dictatorships, and the notion of legitimacy are considered.
Keywords: 330